2020
DOI: 10.20944/preprints202005.0132.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk Perception and COVID-19

Abstract: The ongoing COVID-19 pandemic is shaking the foundations of public health governance all over the world. Researchers are challenged by informing and supporting authorities on acquired knowledge and practical implications. This commentary applies established theories of risk perception research to COVID-19 and reflects on the role of risk perceptions in these unprecedented times. Moreover, it calls for utilizing the knowledge on risk perception to improve health risk communication, build trust and contribute to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
117
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(125 citation statements)
references
References 1 publication
2
117
0
4
Order By: Relevance
“…One in four workers devoted more than three hours a day to learning about COVID-19, and those with psychological distress spent even more time. In previous studies, the most unknown risks are found to be more threatening [ 52 ], while others have shown that less health knowledge is associated with less concern about becoming infected [ 53 ]. The use of preventive measures has also been associated with the level of information [ 45 , 54 ]; more information is associated with perceiving a higher risk and with greater compliance with preventive measures [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…One in four workers devoted more than three hours a day to learning about COVID-19, and those with psychological distress spent even more time. In previous studies, the most unknown risks are found to be more threatening [ 52 ], while others have shown that less health knowledge is associated with less concern about becoming infected [ 53 ]. The use of preventive measures has also been associated with the level of information [ 45 , 54 ]; more information is associated with perceiving a higher risk and with greater compliance with preventive measures [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decisions made by tourists about their chosen activities and travel destinations are influenced by their perceptions of safety and security [ 40 ]. Risk perception is a subjective psychological construct that is influenced by cognitive factors (knowledge and understanding of risks), emotional and experiential factors (personal experience), and social, cultural, and individual factors such as gender, education, and ideology [ 41 , 42 , 43 , 44 ]. In general terms, studies show that the more risk people perceive the less likely they are to visit public places such as beaches and the more likely they are to cooperate with government recommendations and to adopt health-protective behaviors [ 42 , 45 , 46 , 47 , 48 ].…”
Section: Understanding Beachgoer Risk Perceptionmentioning
confidence: 99%
“…The determinants of an individual’s risk perception were their experience with the virus, social amplification (hearing about the virus from friends and family), pro-sociality, individualistic worldviews, self and collective efficacy, trust, and personal knowledge. Other researchers identified the voluntariness of taking the risk to be another factor that negatively affects the perception of risk [ 41 ].…”
Section: Understanding Beachgoer Risk Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rex et al have reported that during the pandemic 44% of patients scheduled for endoscopy were very or somewhat concerned about acquiring infection, while 25% were quite unsure or not willing at all to undergo endoscopy [11]. In an emerging epidemic, human behavioral changes are driven by risk perceptions [7], [12], [13] and this is also related to the psychological status of patients, the self-perception of vulnerability and the perceived severity of symptoms. Our findings demonstrate that patients attending endoscopy during the pandemic were younger than in 2019, a circumstance that can be explained with the perceived higher risk of developing more severe infection in elderly.…”
Section: Resultsmentioning
confidence: 99%